2018
DOI: 10.1371/journal.pone.0204966
|View full text |Cite
|
Sign up to set email alerts
|

Understanding women’s, caregivers’, and providers’ experiences with home-based records: A systematic review of qualitative studies

Abstract: Mothers, caregivers, and healthcare providers in 163 countries have used paper and electronic home-based records (HBRs) to facilitate primary care visit. These standardized records have the potential to empower women, improve the quality of care for mothers and children and reduce health inequities. This review examines experiences of women, caregivers and providers with home-based records for maternal and child health and seeks to explore the feasibility, acceptability, affordability and equity of these inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…There was evidence to suggest that health care workers in low-income settings valued HBRs, and especially integrated multi-focus HBRs, for the information provided, convenience, and long-term value. 7 This was especially true in settings where facility-based record systems were incomplete or incorrect. In addition, studies indicated that HBRs that incorporated not only the data recording function but also the additional health education function provided a common talking point for patients and health care workers, enhancing patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There was evidence to suggest that health care workers in low-income settings valued HBRs, and especially integrated multi-focus HBRs, for the information provided, convenience, and long-term value. 7 This was especially true in settings where facility-based record systems were incomplete or incorrect. In addition, studies indicated that HBRs that incorporated not only the data recording function but also the additional health education function provided a common talking point for patients and health care workers, enhancing patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of the evidence synthesis for the World Health Organization (WHO) recommendations on HBRs for MNCH 3 alongside a quantitative systematic review and meta-analysis of peer-reviewed literature 6 and a qualitative review of peer-reviewed literature. 7 The guidelines, published in September 2018, recommend HBRs as a tool to improve MNCH outcomes. 3 Studies summarized within the quantitative review and meta-analysis found that HBRs had statistically significant effects on improving antenatal care attendance and supportive household environments; however, the evidence base is small and of low to very low certainty.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations